Incasarus garciai, a new genus and species of panurgine bees from the Peruvian Andes (Hymenoptera: Andrenidae) - Gonzalez, Victor H.; Rasmussen, Claus; Engel, Michael S. (Journal of Melittology, 2013)
Incasarus garciai Gonzalez, Rasmussen, & Engel, a new genus and species of protandrenine bees (Andrenidae: Panurginae), is described and figured from a male collected in Ayacucho, Peru. Incasarus superficially resembles Liphanthus Reed in the narrow pterostigma and gonostylus articulated to the gonocoxite but it can be distinguished easily by the combination of two submarginal cells, the seventh sternum with apodemes and apical lobes broad, short, attached to a large disc, and the gonostylus long, about as long as the gonocoxite. Incasarus also resembles Rhophitulus Ducke and Heterosarus Robertson in the male seventh tergum with the distal margin medially projected, but it differs from both genera in the shape of the hidden sterna and genitalia, among other features.